Language anxiety and language processing - Mihaljević Djigunović, Jelena (Array, 2006)
In this chapter the author addresses the following issues concerning the relationship of language use anxiety and language processing: what effect does language anxiety have on processing during L1 and L2 use? ; what effect does language anxiety have on L2 processing as compared to L1 processing? ; how are different anxiety-inducing conditions perceived by language users while using L1 and while using L2?. In the study the author compares language processing in L1 (Croatian) and L2 (English) by control and experimental group subjects during two communicative tasks. The tasks involved picture descriptions, one in L1 and one in L2. The experimental group was subjected to three anxiety-inducing conditions. In order to get a broader view of what might be relevant for understanding the effects of language anxiety on language processing data on the following characteristics of subjects were collected from both groups: trait anxiety ; language use anxiety ; communication apprehension ; willingness to communicate ; L1 proficiency ; L2 proficiency ; self-rating of L2 skill, motivation and aptitude. Before each picture description task the subjects' task motivation and state anxiety were measured. Following each task, measures of cognitive interference during the task and post-task state anxiety were collected from both groups. The experimental group subjects were also asked to fill in a questionnaire that measured the impact of the three anxiety-provoking conditions. The oral performances in both groups were audio recorded. Broad-based analyses of the subjects' oral picture descriptions were made to identify patterns in their language processing. These were interpreted against the relevant language user characteristics whose measures were included in the study. Attempts at tentative answers were made on the basis of the findings.